2011
DOI: 10.5424/sjar/20110902-235-10
|View full text |Cite
|
Sign up to set email alerts
|

Traffic effect on soil compaction and yields of wheat in Spain

Abstract: The general objective of this paper was to quantify the changes in the physical properties of an Aridisol soil and the effect on wheat yield due to agricultural tractors traffic in the Vélez Blanco District, Almería Spain. Parameters measured were cone index (CI) in the 0-600 mm depth profile, bulk density (BD) and rut depth; the variable wheat yields (WY) was measured too. The traffic treatments applied were: 0 (control plot), 1, 3, 5, and 7 tractor passes in the same tracks. Each experimental plot was traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…M édias seguidas de mesma letra na coluna não diferem entre si, pelo teste de Tukey, ao nível de 10% de probabilidade. TOLON-BECERRA et al, (2011), avaliando o efeito do tráfego de um trator leve e um pesado na compactação do solo, observaram que, entre 0,0 e 0,20 m de profundidade, o índice de cone e a densidade do solo responderam à pressão aplicada ao solo tanto para uma passada dos tratores, quanto para 3 e 5, sendo os maiores valores absolutos obtidos para o trator leve, o que foi justificado pelos autores pela menor área de contato pneu-solo apresentada por este.…”
Section: Resultsunclassified
“…M édias seguidas de mesma letra na coluna não diferem entre si, pelo teste de Tukey, ao nível de 10% de probabilidade. TOLON-BECERRA et al, (2011), avaliando o efeito do tráfego de um trator leve e um pesado na compactação do solo, observaram que, entre 0,0 e 0,20 m de profundidade, o índice de cone e a densidade do solo responderam à pressão aplicada ao solo tanto para uma passada dos tratores, quanto para 3 e 5, sendo os maiores valores absolutos obtidos para o trator leve, o que foi justificado pelos autores pela menor área de contato pneu-solo apresentada por este.…”
Section: Resultsunclassified
“…Douglas (1994) reported that the vast majority of research findings up to that date have indicated a strong negative relationship between wheel-induced soil compaction and herbage dry matter yield. Tolon-Becerra et al (2011) working with a wheat crop recorded trafficked zone yield decreases of 18, 22, 30 and 38% following 1, 3, 5 and 7 passes, respectively, of a heavy tractor (8160 kg) when compared with the untrafficked control. In short rotation coppice willow, heavy compaction reduced stem biomass production byapproximately 12% overall and increased soil strength and bulk density down to a depth of 40 cm (Souch et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…Also the adverse effects of high axle load on compaction have been reported by Duiker [31], Hakansson et al [32] and Arvidsson [33], Alakukku [17], Botta et al [34] and Tolon-Becerra et al [16] reported on the negative effects of intensity of traffic on compaction while Hamza et al [35] Forristal [36] and Schjønning et al [37] reported on the negative effects of inflation pressure on compaction.…”
Section: Soil Compactionmentioning
confidence: 92%
“…Tolon-Becerra et al [16] working with wheat (Triticum spp.) recorded trafficked yield decreases of 18%, 22%, 30% and 38% following 1, 3, 5 and 7 passes respectively of a heavy tractor (8160 kg) when compared with the untrafficked control.…”
Section: Introductionmentioning
confidence: 99%